Cdc42 regulates schwann cell radial sorting and myelin sheath folding through NF2/merlin‐dependent and independent signaling. Issue 11 (6th September 2013) - Guo, Li; Moon, Chandra; Zheng, Yi; Ratner, Nancy
<x xml:space="preserve">Abstract</x> The Rho family GTPase Cdc42 has been implicated in developmental Schwann cell (SC) proliferation, providing sufficient SCs for radial sorting of axons preceding SC differentiation in the peripheral nervous system. We generated Cdc42 conditional knockout (Cdc42‐CKO) mice and confirmed aberrant axon sorting in Cdc42‐CKO nerves. In adult Cdc42‐CKO nerves, blood vessels were enlarged, and mature Remak bundles containing small axons were absent. Abnormal infoldings and outfoldings of myelin sheaths developed in Cdc42‐CKO nerves, mimicking pathological features of Charcot‐Marie‐Tooth (CMT) disease. The NF2/merlin tumor suppressor has been implicated up‐ and down‐stream of Cdc42. In Cdc42‐CKO;NF2‐del double mutant mice, radial sorting defects seen in Cdc42‐CKO nerves were rescued, while changes in myelin sheaths in Cdc42‐CKO nerves were not. Phosphorylation of Focal adhesion kinase (FAK) and P‐GSK3β, as well as expression of β‐catenin were decreased in Cdc42‐CKO nerves, and these changes were rescued by NF2/merlin mutation in Cdc42‐CKO;NF2‐del double mutant mice. Thus, Cdc42 regulates SC radial sorting in vivo through NF2/merlin dependent signaling pathways, while Cdc42 modulation of myelin sheath folding is NF2/merlin independent. GLIA 2013;61:1906–1921